The role of self-awareness and learning discipline during distance learning in urban students - Eka Putri Azrai; Erna Heryanti; Nandita Fazriati (Universitas Negeri Jakarta, 2026)
Conceptual understanding is an essential component in achieving meaningful learning outcomes in biology. During distance learning, students are required to regulate their learning independently, making self-awareness and learning discipline important factors that may influence their conceptual understanding. This study aimed to examine the role of self-awareness and learning discipline in distance learning in improving students’ conceptual understanding of drug-related material among urban high school students. The research employed a quantitative descriptive correlational design. The study was conducted in a public high school in Jakarta, Indonesia, involving 85 grade XII science students selected through simple random sampling. Data were collected using validated instruments measuring self-awareness, learning discipline, and conceptual understanding. Data analysis included descriptive statistics, prerequisite tests, and regression analysis. The results showed that students’ self-awareness and learning discipline were generally in the high category. Regression analysis indicated that self-awareness and learning discipline together contributed 7.1% to students’ conceptual understanding of drug material, while 92.9% was influenced by other factors. These findings suggest that although self-awareness and learning discipline play a role in supporting conceptual understanding during distance learning, other internal and external factors should also be considered to improve students’ learning outcomes.